1976
DOI: 10.1148/119.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Diverticulum of the Hepatic Duct: A Rare Anomaly

Abstract: A diverticulum of the hepatic duct was found in a 25-year-old woman. Cholangiography revealed that the diverticulum was cystic in nature and contained several stones. Since the intrahepatic ducts are never seen at surgery, the authors stress the importance of preoperative and operative cholangiography in locating such anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…None of the previously published cases described ABPDU. 8,9,11,12 Various imaging modalities for preoperative evaluation of choledochal cyst are now available, such as CT, MRCP, ultrasonography, hepatobiliary scan, percutaneous transhepatic cholangiography, and endoscopic retrograde cholangiopancreatography (ERCP). 13 Hepatic duct diverticula can be confused with other cystic lesions such as hepatic cysts, enteric duplication cysts, hepatic artery aneurysm, and duplication anomalies of gall bladder.…”
Section: Discussionmentioning
confidence: 99%
“…None of the previously published cases described ABPDU. 8,9,11,12 Various imaging modalities for preoperative evaluation of choledochal cyst are now available, such as CT, MRCP, ultrasonography, hepatobiliary scan, percutaneous transhepatic cholangiography, and endoscopic retrograde cholangiopancreatography (ERCP). 13 Hepatic duct diverticula can be confused with other cystic lesions such as hepatic cysts, enteric duplication cysts, hepatic artery aneurysm, and duplication anomalies of gall bladder.…”
Section: Discussionmentioning
confidence: 99%
“…While its incidence is very low, its true incidence may be difficult to determine because it is generally of no clinical significance and thus requires no specific treatment [4,5]. Eisendrath [6] reported that similar hepatic duct anomalies can be found in 8% of autopsies, indicating that almost all cases must be asymptomatic and are incidental.…”
Section: Discussionmentioning
confidence: 99%
“…Diverticulum of the common bile duct may undergo spontaneous rupture with formation of retroperitoneal biloma (Takahashi et al 2005). Diverticula have rarely been observed in the hepatic duct (Eisen et al 1963;Jackson and Maxwell 1964;Maxwell et al 1967;Napoli 1970;Down 1974;Meyers et al 1976;Schey et al 1977;Farkas et al 1980;Flowers and Ho 1998;Kaneyama et al 2005a;Hashimoto et al 2007;Fernandes et al 2010). Hepatic duct diverticulum may occur in the common hepatic duct (hepatodochal diverticulum) or in the left or right hepatic duct and is considered to be a developmental anomaly.…”
Section: Diverticula Of Bile Ducts Congenital Diverticula Of the Bilimentioning
confidence: 99%